Experimental studies of the process of additive electric arc forming in the environment of protective gases - Grechukhin, A. N.; Privalov, A. S.; Garkavtseva, P. A. (AIP conference proceedings, 2019)
Questions are considered about the accuracy of the formation of the surface layer by additive methods. The analysis of works is carried out on a research subject. High values of the error of forming (approximation) are revealed at forming of surfaces of a complex profile by additive methods. The spatial orientation of a single layer is proposed to reduce the error of forming products by additive methods. Mathematical dependences are proposed to determine the value of the parameters of a single directed layer on the results of experimental studies.